KEANEKARAGAMAN JENIS TUMBUHAN OBAT DI TAMAN NASIONAL SEBANGAU (Biodiversity of Medicinal Plants at the Sebangau National Park) : Christopheros1, Yusintha Tanduh1, Andrico Budi Saputra Panjaitan2 - Admin JHT (Jurnal Hutan Tropika, 2017)
ABSTRACT Medicinal plants were used as medicine and traditional treatment since thousand years ago in Indonesia. Indonesia itself has more than 1000 species of plants which were used as raw material to produce natural medicinal plants by Industry of traditional medicine. When the number of population increased further, it was expected that use of medicinal plants supported medical treatment. The diversity of plants in Indonesia was one of natural wealth which need to be preserved since their role and benefits could bring advantages for society in form of treatment and health care. Sebangau National Park was object to study of medicinal plants. This study was aimed to find out the diversity of medicinal plants species from level of seedling, sapling, poles and tree at around Tumbang Bulan, Teluk Beruang River, and Sebangau National Park in Katingan Regency, Central Kalimantan Province. The determination of sample plot was conducted using purposive sampling in areas of 2 ha. The observation was conducted in two lines. Every growth level of underground plant, seedling, sapling, poles and tree was made within 50 sub sample plots, afterward the data was collected and analyzed to find out Important Value Index (IVI), Species Diversity Index (H’), Species Richness Index (R), and Homogenous Index (E). Research result showed that there are 13 species medicinal plants that founded in research location, i.e. asam-asam, akar kuning, akar kalalawit, belawan merah, gemor, jinjit, kapur naga, kantong semar, kemuning, keripak, mangkinang tikus, meranti and terentang. Each growth level was dominated by jinjit. Value of species diversity index (H’) for level of seedling was 1.98, meanwhile the values of sapling, poles and tree were about 2.05 to 2.24 which included in moderate category. Value of species richness index (R) was dominated by growth level of seedling namely 1.68, meanwhile at the growth level of sapling, pole and tree were 1.54, 1.56, and 1.59 respectively. Value of homogenous index (E) for all growth levels were in high category, namely within range 0.80 to 0.97. Keywords: Important value index, purposive sampling species diversity